Efektivitas Beberapa Jenis Feromon Organik Sebagai Atraktan Lalat Buah Pada Tanaman Cabai - Fendi Andiko; Muhammad Indar Pramudi; Samharinto Soedijo (JURNAL PROTEKSI TANAMAN TROPIKA, 2023)
Red chili (Capsicum annuum L.) is a commodity that has high economic value, but the potential loss experienced in chili cultivation is also quite high, because chili is quite vulnerable to fruit fly pests. This study aims to determine the response of fruit flies to the use of pheromones derived from various kinds of fruit peels and flesh added with yeast (organic pheromones). This research took place on chili farmers' land located in the village of Tambak Langsat, West Ulin Platform, Banjarbaru City. This study used a randomized block design (RBD) with 11 treatments including the control. The results showed that the treatment given organic pheromones was able to trap fruit flies. Of all the pheromones that were most effective at getting lots of fruit flies was the chili pheromone (0.2 ml) with a catch of 25 individuals and for organic pheromones that were less effective was the mango pheromone (0.2 ml) with a catch of 4 individuals. The type of fruit fly B. dorsalis dominates of the four species with the Diversity Index (H´) of fruit flies being classified as moderate, namely 1.1082, the Dominance Index (D) being high 1 and for fruit flies dominating B. dorsalis.